The Status and Improvement of Pet Management of Non-State Key Protected Wildlife - Li, Mingxuan (International Journal of Social Sciences and Public Administration, 2025)
According to the Wildlife Protection Law, protected wildlife refers to rare and endangered terrestrial and aquatic wildlife and terrestrial wildlife of important ecological, scientific and social value. Wild animals are protected with the precious and endangered degree and value of wildlife, and non-such wildlife is not within the protection scope stipulated in the Wildlife Protection Law. At the same time, there is also a vacuum in the illegal operation and utilization of wildlife under non-state key protection. As an emerging way of management and utilization of non-state key protected wildlife, pet management is controversial in legal regulation. Through the analysis of the present situation of the state protection wildlife, combing the cause of the present situation, and combined with the wildlife protection law and the regulations on the implementation of terrestrial wildlife protection (hereinafter referred to as the regulations), put forward reasonable countermeasures, aims to improve the legal system of wildlife protection, improve the status of the state protection wildlife protection, comprehensive protection of wildlife in our country.